Bay Breeze and Sea Breeze Circulation Impacts on the Planetary Boundary Layer and Air Quality From an Observed and Modeled DISCOVER‐AQ Texas Case Study. Issue 13 (2nd July 2019) - Caicedo, V.; Rappenglueck, B.; Cuchiara, G.; Flynn, J.; Ferrare, R.; Scarino, A. J.; Berkoff, T.; Senff, C.; Langford, A.; Lefer, B.
Abstract: The role of the sea/bay breeze in the planetary boundary layer evolution and air quality during a high ozone event day in the Deriving Information on Surface Conditions from Column and Vertically Resolved Observations Relevant to Air Quality (DISCOVER‐AQ) Texas 2013 campaign was examined. Data from surface air quality monitoring network stations, airborne lidar data, and additional ground‐based lidar instrumentation deployed during the campaign allowed for a unique three‐dimensional spatial and temporal study of the progression of both meteorological and air quality conditions in the Houston‐Galveston regions on 25 September 2013. The Weather Research and Forecasting model coupled with Chemistry model was used to examine the relationship of the land and bay/sea breeze circulations and its influence on air quality during the case study. Comparisons between observations and simulations revealed the largest discrepancies near the Galveston Bay shore areas where the highly localized ozone concentrations were observed and were linked to the strength and timing of the bay/sea breeze progression. Additionally, results indicate vertical downmixing from the remnants of the nighttime residual layer during morning hours into the convective boundary layer and from the lofted offshore return flow into the subjacent bay breeze flow. Key Points: Sea/bay breeze role in the planetary boundary layer evolution and air quality during a high ozone event Model simulations and observation comparison revealed the largest discrepancies near Galveston Bay shoreline Localized ozone was linked to breeze progression with possible contributions from residual layer and the lofted offshore return flow